Interspecies Relational Theory: A Framework for Compassionate Interspecies Interactions - Emily Kieson (Veterinary Sciences, 2025)
Most studies on relationships between humans and nonhuman animals focus on the benefits of the relationship to humans, the potential detriment or stress to animals, or how humans can better improve husbandry or handling practices in the domestic setting. By comparing existing research in human working relationships and friendships with animal friendships and studies on human–animal interactions, this paper proposes a new framework of an Interspecies Relational Theory that provides approaches for identifying, developing, and maintaining different levels of relationships between humans and nonhuman species. The framework is broken into three stages aligned with existing research in human levels of trust ranging from strategic/calculus-based to working/knowledge/information-based to friendship/affect-based. These levels are also aligned with stages of Maslow’s Hierarchy. The suggested framework can help provide insight into both human and animal perspectives of the human–animal relationship in a variety of veterinary and animal-assisted settings.